Effect of LH Hormone on Premenstrual Syndrome in Female Adolescents at Darul Arqam Islamic Boarding School Makassar - Ruqaiyah Ruqaiyah; Ayatullah Harun; Hadriani Irwan; Fatmawati Amir; Ikrawanty Ayu Wulandari; Alamsyah Alamsyah (Universitas Aisyah Pringsewu, 2023)
This study aims to determine the effect of LH on premenstrual syndrome in young women at Darul Arqam Makassar. The research method used was the t-test to see the effect of LH concentrations on young women who experienced and did not experience premenstrual syndrome. The population of this study were all young women at the Darul Arqam Makassar Islamic Boarding School. The sample used was 50 young women consisting of 25 young women with PMS and 25 young women who were not. The results showed that there was an influence of the LH hormone with the average value of respondents whose average LH value was 7.36, which was higher than that of PMS, which was 7.35. After the data is processed with the t-test obtained p= 0.000 less than 0.05. This means that there is a significant effect of LH hormone concentration between no PMS, mild PMS, and severe PMS. The conclusion is that there is a significant effect of the concentration of the hormone LH f2a among young women who do not have PMS and PMS and between young women who experience mild PMS and severe PMS at Darul Arqam Islamic Boarding School Makassar.